PERTANGGUNGJAWABAN PIDANA KORPORASI DALAM SISTEM HUKUM PIDANA INDONESIA PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Briski Viktor H. Sinaga; Sumarno; Suci Ramdani; Derta Simbolon; Lume Hetty Alphani Simbolon; Rika Suryana Surbakti (CV. Lafadz Jaya, 2026)
The development of modern economic activities has significantly strengthened the role of corporations as legal entities that contribute substantially to national economic growth and development. However, corporations also possess the potential to become perpetrators of various criminal offenses, including corruption, money laundering, tax crimes, environmental crimes, consumer protection violations, and other economic crimes. The enactment of Law Number 1 of 2023 concerning the Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) marks a fundamental reform in Indonesia's criminal law by explicitly recognizing corporations as subjects of criminal liability. This legal reform provides a more comprehensive framework governing the concept, forms, and mechanisms of corporate criminal liability within the Indonesian criminal justice system. This study aims to analyze the regulation of corporate criminal liability in Indonesia's criminal law system, examine the forms of corporate criminal liability under Law Number 1 of 2023, and identify the challenges and optimization efforts in implementing corporate criminal liability. This research employs a normative legal research method using a statutory approach, conceptual approach, case approach, and comparative approach. The legal materials consist of primary, secondary, and tertiary legal sources collected through library research. The collected legal materials are analyzed qualitatively using descriptive-analytical and prescriptive methods to formulate legal arguments regarding corporate criminal liability in Indonesia's criminal law system. The findings indicate that the regulation of corporate criminal liability in Indonesia has undergone significant development through Law Number 1 of 2023, which explicitly recognizes corporations as subjects of criminal law. Criminal liability may be imposed on the corporation itself, its management, or both simultaneously, depending on the degree of fault, the relationship between the offender and the corporation, and the benefits obtained by the corporation from the criminal act. In addition to fines as the principal punishment, corporations may also be subjected to additional penalties and corrective measures, including confiscation of criminal proceeds, compensation for victims, revocation of business licenses, suspension of business activities, restitution for damages caused by criminal acts, and, in certain circumstances, corporate dissolution. Nevertheless, the implementation of these provisions continues to face several challenges, including inconsistencies between the Criminal Code and sector-specific legislation, difficulties in proving corporate mens rea, limited institutional capacity of law enforcement agencies, and the absence of comprehensive technical guidelines for handling corporate criminal cases. Therefore, regulatory harmonization, institutional capacity building for law enforcement officers, the development of comprehensive implementation guidelines, and the strengthening of good corporate governance and corporate compliance principles are essential to establishing an effective corporate criminal liability system that ensures legal certainty, justice, and public benefit.